Decoding Asian Urbanism - Ameen, Farooq (MAJ - Malaysia Architectural Journal, 2025)
The rapid pace of urbanization in 21st-century Asia is driven by a profound demographic shift toward urban centers, spurred by the pursuit of prosperity. This phenomenon aligns with Edward Glaeser’s thesis in The Triumph of the City, which argues that urban connectivity is the most direct route from poverty to wealth. The scale of this urban expansion is remarkable, with a fivefold increase in the number of Asian cities boasting populations exceeding five million within just five decades. Meanwhile, entirely new cities are being developed from the ground up, covering extensive areas and challenging traditional timelines of urban development. However, this rapid urban growth poses the risk of cultural homogenization, as many developments replicate Western models that may not be suited to Asia’s diverse contexts. These standardized approaches often exacerbate issues such as social inequality, alienation, and environmental degradation. In response, the initiative "deCoding Asian Urbanism" seeks to identify design and planning principles that genuinely address the transformative trajectory of Asian cities. The initiative underscores the importance of crafting interventions that balance the demands of rapid growth and large-scale development with the preservation of cultural identity. This research engages with fundamental questions, aiming to uncover the unique characteristics of Asian cities and explore how they can implement effective urban interventions while maintaining their distinct identities.